Influence of Birth Weight on the Renal Development and Kidney Diseases in Adulthood: Experimental and Clinical Evidence - Maria C. P. Franco; Vanessa Oliveira; Beatriz Ponzio; Marina Rangel; Zaira Palomino; Frida Zaladek Gil (International Journal of Nephrology)
Several clinical and experimental studies support the hypothesis that foetal programming is an important determinant of nephropathy, hypertension, coronary heart disease, and type 2 diabetes during adulthood. In this paper, the renal repercussions of foetal programming are emphasised, and the physiopathological mechanisms are discussed. The programming of renal diseases is detailed based on the findings of kidney development and functional parameters.